2006
DOI: 10.1111/j.1469-1809.2006.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Disorder of Glycosylation Type Ia: Searching for the Origin of Common Mutations in PMM2

Abstract: SummaryCongenital Disorders of Glycosylation (CDG) are a group of recessive genetic disorders characterized by hypoglycosylation of glycoproteins. CDG-Ia, the most common type, is caused by mutations in the PMM2 gene, coding for a phosphomannomutase (PMM2; EC 5.4.2.8). The mutational spectrum of PMM2 comprises more than 80 different mutations but one of them, R141H, is particularly interesting due to its high frequency among CDG-Ia patients worldwide. In contrast, other mutations are ethnically or geographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Of these 30 identified mutations, 13 have only been reported in our series of patients. The p.D65Y mutation was reported in a French study in a Portuguese patient, and a haplotypic association study confirmed its Iberian origin (Quelhas et al 2007), and the p.V44A mutation was reported in an Ecuatorian patient probably of Spanish ancestors, adding these two mutations to our population-specific group of mutations. It is to note that mutations p.N216I and p.T226S were also previously reported in patients of Mediterranean origin (France, Italy, and Greece) .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Of these 30 identified mutations, 13 have only been reported in our series of patients. The p.D65Y mutation was reported in a French study in a Portuguese patient, and a haplotypic association study confirmed its Iberian origin (Quelhas et al 2007), and the p.V44A mutation was reported in an Ecuatorian patient probably of Spanish ancestors, adding these two mutations to our population-specific group of mutations. It is to note that mutations p.N216I and p.T226S were also previously reported in patients of Mediterranean origin (France, Italy, and Greece) .…”
Section: Resultsmentioning
confidence: 84%
“…A large variety of mutations have been identified in our Iberian cohort of unrelated PMM2-CDG patients: 25 (83%) are missense mutations (Briones et al 2002;Quelhas et al 2007), four of them newly reported here (p.Y102C, p.T118S, p.P184T, and p.D209G); one nonsense (p.R123X) (Briones et al 2002), three affecting the splicing of mRNA (IVS3+ 2T>C; IVS3-1G>C and IVS7-9T>C) (Briones et al 2002;Vega et al 2009), and a deletion mediated by an Alu retrotransposition displaying the complete loss of exon 8 (Schollen et al 2007a). Of these 30 identified mutations, 13 have only been reported in our series of patients.…”
Section: Resultsmentioning
confidence: 99%
“…The carrier frequency of this variant ranges from 1 in 72 to 224 in Northern European populations (Schollen, Kjaergaard, Legius, Schwartz, & Matthijs, ; Vals et al, ), but is 1 in 1,311 in our sample. The high frequency of the p.Arg141His variant in Europe is attributed to heterozygote advantage against hepatitis viruses (Freeze & Westphal, ), but there is also evidence that it descends from a single origin before recombining into different haplotypes (Quelhas, Quental, Vilarinho, Amorim, & Azevedo, ). It is predominantly the high prevalence of this variant that contributes to the relatively high estimated prevalence of PMM2‐CDG (1:20,000) (Schollen et al, ), which is much higher than that calculated from our sample (1:286,726).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical heterogeneity present in PMM2‐CDG patients, along with the practical absence of homozygosity among the studied patients, hinders a straightforward genotype–phenotype correlation for this disease. After the analysis of the reported genotypes carrying the studied mutations, we can conclude that just destabilizing mutations retaining residual activity have been detected in homozygosity, such as p.T237M and p.D65Y [Grunewald et al., ; Quelhas et al., ; Vega et al., ]. Furthermore, among the studied mutants, p.R162W and p.T237M have been associated with mild or moderate phenotypes [Grunewald et al., ; Quelhas et al., ), whereas p.V44A and p.D65Y have been related with more severe phenotypes [Grunewald et al., ; Quelhas et al., ; Schollen et al., ].…”
Section: Discussionmentioning
confidence: 99%